Migrants, Towns, Poverty and Jobs : Insights from Tanzania - Christiaensen, Luc (World Bank, Washington, DC, 2018)
For a long time, the urbanization and development discourse has coincided with a focus on economic growth and big cities. Yet, much of the world's new urbanization is taking place in smaller urban entities (towns), and the composition of urbanization may well bear on the speed of poverty reduction. This paper reviews the latter question within the context of Tanzania. It starts from the observation that migration to towns contributed much more to poverty reduction than migration to cities because many more (poor) rural migrants ended up in Tanzania's towns than its cities, despite larger welfare gains from moving to the city. Drawing on the findings from a series of studies, looking at this from different angles (theoretical and empirical, quantitative and qualitative), the paper shows how towns are better at enabling the rural poor to access off-farm employment and exit poverty because they are more nearby. It concludes with a call for greater consideration of the role of towns in accelerating Africa's poverty reduction.